2014
DOI: 10.1038/ajg.2014.171
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Outcomes of Interval Colorectal Cancers: A Systematic Review and Meta-Analysis

Abstract: Based on meta-analysis, approximately 1 in 27 CRCs are interval CRCs, although the confidence in these estimates is low because of the heterogeneity among the studies. These are more likely to arise in the proximal colon and are diagnosed in older patients, patients with comorbidities or diverticular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
208
4
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(233 citation statements)
references
References 43 publications
15
208
4
6
Order By: Relevance
“…2 There are many factors that increase CRC risk, including age, diet, ethnic background, known genetic alterations, family history of the disease, and chronic colon inflammation (colitis). 3 Mouse and rat models developed to study CRC have confirmed some of the risk factors elucidated from human cases. These models also revealed many of the molecular events underlying different risk factors and interactions between various risk factors.…”
Section: Introductionmentioning
confidence: 89%
“…2 There are many factors that increase CRC risk, including age, diet, ethnic background, known genetic alterations, family history of the disease, and chronic colon inflammation (colitis). 3 Mouse and rat models developed to study CRC have confirmed some of the risk factors elucidated from human cases. These models also revealed many of the molecular events underlying different risk factors and interactions between various risk factors.…”
Section: Introductionmentioning
confidence: 89%
“…However, a fraction of people develop colorectal cancer between the index and subsequent surveillance procedures. In a meta-analysis of 12 observational studies, the pooled prevalence of interval cancer was 3.7% [95% confidence interval (CI), 2.8-4.9%] among all colorectal cancer cases (1). This analysis also suggests that interval cancer is more likely to be located in the proximal colon, and old age and positive family history of colorectal cancer are potential risk factors (1).…”
mentioning
confidence: 94%
“…Post-colonoscopy colorectal cancer or so-called "interval cancer" has emerged as one of new research topics, attracting much attention of endoscopists, gastroenterologists, and oncologists alike (1)(2)(3)(4). In addition to lesions missed during the index colonoscopy due to technical issues (e.g., skills of endoscopists, quality of bowel preparation) or tumor morphology (e.g., sessile serrated adenoma/polyps) (5), some tumors arising after colonoscopy may have rapidly-growing biological behavior with distinct molecular and pathological features (1)(2)(3)(4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review on interval colorectal cancers, that is, cancers that are thought to have been missed on colonoscopy and presented within a year, suggested that there was an increased risk of proximal cancer with diverticular disease, the interpretation being that diverticula may cause technical difficulty to perform a complete colonoscopy rather than any other biologically based explanation. [5] The issue of missed cancer diagnosis in case of coexistent diverticulitis has been suggested also by a review of 633 CT scans, in 17 cases an unsuspected bowel cancer was later found. [6] The main supporting studies have been epidemiological cohort series from database registers.…”
Section: Diverticular Disease and Cancer: An Unproven Linkmentioning
confidence: 99%